"Exploring barriers to citizen participation in development: a case study of a participatory broadcasting project in rural Malawi" - Mtelera, Prince (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2014)
In Malawi, as in many newly-democratic countries in the developing world, donor organisations and NGOs have embarked on projects aimed at making reforms in governance which have generated a profusion of new spaces for citizen engagement. This thesis critically examines one such project in Malawi against the backdrop of a democratic nation emerging from a background of dictatorial regime. For thirty years, until 1994, Malawi was under the one-party regime of Kamuzu Banda which was characterised by dictatorial tendencies, in which participatory processes were non-existent and development was defined in terms of client-patronage relationships between the state and society (Cammack, 2004: 17). In 1994, however, Malawi embraced a multiparty system of government, paving way to various political and social reforms, which adopted participatory approaches to development. Drawing on a number of literatures, this thesis seeks to historicize the relationship which developed during the pre democracy era between the state and society in Malawi to underscore its influence on the current dispositions displayed by both bureaucrats and citizens as they engage in participatory decision making processes. This is achieved through a critical realist case study of a participatory radio project in Malawi called Ndizathuzomwe which works through a network of community-based radio production structures popularly known as 'Radio Listening Clubs'(RLCs) where communities are mobilised at village level to first identify and define development problems through consensus and then secondly engage state bureaucrats, politicians, and members of other relevant service delivery organisations in making decisions aimed at resolving community-identified development problems (Chijere-Chirwa et al, 2000). Unlike during the pre-democracy era, there is now a shift in the discourse of participation in development, from the participation of 'beneficiaries' in projects, to the more political and rights-based definitions of participation by citizens who are the 'makers and shapers' of their own development (Cornwall and Gaventa, 2000). The findings of this thesis, however point to the fact that, there remains a gap between normative expectations and empirical realities in that spaces for participation are not neutral, but are themselves shaped by power relations (Cornwall, 2002). A number of preconditions exist for entry into participatory institutions as such entry of certain interests and actors into public spaces is privileged over others through a prevailing mobilisation of bias or rules of the game (Lukes, 1974: I)
Keywords: Political participation -- Malawi; Malawi -- Citizen participation; Citizen journalism -- Malawi